Parâmetros hidráulicos e fotossintéticos de espécie lenhosa do Cerrado mato-grossense - Prado, Magdiel Josias do (2019)
The acclimatization capacity in plant species given the pronounced water scarcity has been one of the issues addressed in studies of global climate change. Native Cerrado species have experienced extreme variations in soil water supply throughout their development due to seasonality in rainfall and soil characteristics. These variations require different strategies from the species that allow them both hydraulic safety and maximization of carbon gain. In this study, we assess the cavitation resistance expressed by P50, the hydraulic safety margin (MSH) and the strategy for regulating the variations in water potential (iso / anisohydric) of the species Hymenaea stigonocarpa Mart. The results show that the species presented an MSH of 0.4MPa, which indicates that the species is susceptible to vessel cavitation; However, the risk of hydraulic collapse is low, considering the decidua characteristic of the species as a complementary strategy to excessive water loss during periods of greater water restriction. The strategy of regulating the variations of water potential, described by the behavior of the gas exchange variables (A, gs and E) against the variations of the environmental variables (PAR, T, DPV and ΨM) point to different seasonal strategies in the regulation of the variations. of water potential. These differences are mainly evidenced by the relative constancy in the values associated with the gas exchange variables in view of the significant variations of Ψf and the soil water supply.